Epidemiological update on the dengue situation in the Western Pacific Region, 2012 - Yuzo Arima; May Chiew; Tamano Matsui (World Health Organization Regional Office for the Western Pacific, 2015)
Dengue has caused a substantial public health burden in the Western Pacific Region. To assess this burden and regional trends, data were collated and summarized from indicator-based surveillance systems on dengue cases and deaths from countries and areas in the Western Pacific Region. In 2012, dengue notifications continued to increase with 356 838 dengue cases reported in the Region (relative to 244 855 cases reported in 2011) of which 1248 died. In the Asia subregion, the notification rate was highest in Cambodia, the Philippines and the Lao People's Democratic Republic (316.2, 198.9 and 162.4 per 100 000 population, respectively), and in the Pacific island countries and areas, the notification rate was highest in Niue, the Marshall Islands and the Federated States of Micronesia (8556.0, 337.0 and 265.1 per 100 000 population, respectively). All four serotypes were circulating in the Region in 2012 with considerable variabilitiy in distribution. Regional surveillance provides important information to enhance situational awareness, conduct risk assessments and improve preparedness activities.